Análise do processo de adoção de princípios e práticas agroflorestais em áreas de plantio do Centro Espírita Beneficente União do Vegetal - Menezes Neto, Jayme Bezerra de (2024)
This thesis explores the trajectory and practices of the União do Vegetal (UDV), a Brazilian ayahuasca religion that makes sacramental use of Hoasca Tea. The research sought to clarify some causes, such as environmental preservation, sustainability of production systems and valuing the culture and tradition of the UDV are relevant motivations for making people aware of the importance of using SAFs as a planting model by the religious organization. The results indicate that the adoption of these practices is influenced by a variety of complex factors, including, on the one hand, still a lack of knowledge about what agroforestry is and what the principles of agroforestry are, through to resistance to change, and the advantage of having people with extensive experience in agroforestry practices participating in the process of incorporating Agroforestry Systems into the UDV's planting areas. Finally, the thesis analyzes the challenges and results of the UDV's adoption of agroforestry practices, using SWOT/FOFA analysis, a strategic method for analyzing scenarios and making decisions, looking at aspects related to Strengths, Opportunities, Weaknesses and Threats. To overcome the challenges, the research makes some suggestions such as investing in education, training and technical and financial support. This research uncovers the rich web of relationships between faith, sustainability and cultural preservation in the adoption of Agroforestry Systems (SAFs) by the União do Vegetal (UDV). Through a comprehensive analysis, the thesis reveals the UDV's deep connection with the Amazon and its traditions, showing how the community's worldview finds in SAFs a tool for reconciling ritual needs with the preservation of sacred plants and the ecosystem. The socio-environmental benefits of the UDV's adoption of SAFs are tangible: job creation, food security, community autonomy, preservation of biodiversity, maintenance of water resources and mitigation of climate change. The organizational structure of the UDV, with emphasis on the role of the DPMA, is fundamental to the implementation and monitoring of the SAFs, while faith and the use of Hoasca Tea are intertwined with the community's relationship with nature, configuring the SAFs as spaces for learning and spiritual connection with the forest. The results of the research also indicate that the role of the Department of Planting and the Environment (DPMA) has been crucial to the success of the initiative, since the department's team has been involved in organizing and planning the SAFs, as well as providing technical support and training to community members. The adoption of the SAFs at the UDV is the result of a collective and multifaceted effort, which involves the search for a balance between the spiritual, social and environmental needs of the community